Reconciling perspectives to find solutions - Mockshell, Jonathan; Birner, Regina (DLG-Verlag GmbH, 2020)
There is a longstanding debate among agricultural development stakeholders: state-led versus market-led strategies to transform food systems. While narratives provide an important framework to better understand this policy dichotomy and the choices of decision-makers, they are often neglected in food systems policy-making processes. The authors recommend making use of policy narratives to find a way to solve real-world problems.